2016
DOI: 10.1186/s13041-016-0231-5
|View full text |Cite
|
Sign up to set email alerts
|

RIC-3 expression and splicing regulate nAChR functional expression

Abstract: BackgroundThe nicotinic acetylcholine receptors form a large and diverse family of acetylcholine gated ion channels having diverse roles in the central nervous system. Maturation of nicotinic acetylcholine receptors is a complex and inefficient process requiring assistance from multiple cellular factors including RIC-3, a functionally conserved endoplasmic reticulum-resident protein and nicotinic acetylcholine receptor-specific chaperone. In mammals and in Drosophila melanogaster RIC-3 is alternatively spliced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 33 publications
(41 reference statements)
2
32
0
Order By: Relevance
“…This together with the known role of RIC-3 in α7 nAChR maturation suggests that RIC3 variants may affect MS via their effects on α7 nAChR maturation in immune cells. Importantly, we demonstrated that ric3 expression in immune cells is dynamically regulated following immune activation 31 . Moreover, recent unpublished results show that ric3 expression is transiently reduced in splenocytes and is gradually reduced in spinal cords during EAE progression (Yael BenDavid, unpublished).…”
Section: Ric-3 and Diseases Of The Central Nervous Systemmentioning
confidence: 95%
See 3 more Smart Citations
“…This together with the known role of RIC-3 in α7 nAChR maturation suggests that RIC3 variants may affect MS via their effects on α7 nAChR maturation in immune cells. Importantly, we demonstrated that ric3 expression in immune cells is dynamically regulated following immune activation 31 . Moreover, recent unpublished results show that ric3 expression is transiently reduced in splenocytes and is gradually reduced in spinal cords during EAE progression (Yael BenDavid, unpublished).…”
Section: Ric-3 and Diseases Of The Central Nervous Systemmentioning
confidence: 95%
“…. Recently we showed that these opposite effects on nAChR expression can be achieved using different RIC-3-toreceptor ratios, and that sensitivity of nAChR maturation to this ratio depends on the identity of the nAChR and on the specific RIC-3 isoform (different isoforms are produced by alternative splicing, see below) 31 . Second, RIC-3 was shown to affect different aspects of nAChR maturation depending on identity of the receptor's subunits.…”
Section: Maturation Of Nachrs and The Ric-3 Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…This regulation of RIC-3 expression and splicing is likely to have functional implications as electrophysiology results, summarized above, show either positive or negative effects of RIC- 3 on nAChR expression, depending on RIC-3 expression level, specific RIC-3 isoform, and specific nAChR [5]. …”
mentioning
confidence: 99%